DESENVOLVIMENTO ECONÔMICO, ESTRUTURA E DIVERSIFICAÇÃO PRODUTIVA: uma abordagem voltada para o estado do Maranhão - NEDER, Raquel do Nascimento (2020)
The objective of this work was to conduct a critical discussion of the development process in the State of Maranhão. For this, initially a reading and interpretation of the main currents of thought of the theories of development in general and regional development was elaborated, highlighting among them the approaches of North, Myrdal, Hirshman, Perroux and converging to the focus of the structuralist authors, mainly represented by Celso Furtado, who was used as the main theoretical shield for the empirical analysis. Specifically, in the context of agricultural activities, the most recent economic movement is also marked by a strong increase in productive concentration, with an ever smaller number of producers and companies covering most of the value of production.It is also evident that this development model works as a kind of reproduction of the old export agrarian model, with the specificity that it is largely a model of enclave economy. This means that the income generation of most of these most relevant economic activities in the State does not create an internalized circular flow in its economy. Maranhão’s development was guided by the emphasis and the primacy of large economic projects, under the belief that these would leverage other sectors and spread to the entire socio-economic extension of the State. It appears that the intra-regional inequality of the State of Maranhão can be understood mainly as a result of a historical development process determined by retrograde political and agrarian structures. At the same time, the intensity of the phenomenon of economic concentration in a restricted group of micro-regions of the State is perceived while the rest remains in a situation of socioeconomic stagnation. It is strongly perceived that the agricultural production of the State is subdivided into two main forms: the production of agribusiness (soy, forestry and extensive livestock) and the production of family farming products. The indicators treated show that there is a strong tendency to reduce the capacity to incorporate work for these activities.The State of Maranhão, in the period from 2006 to 2017, saw a profound change in its structure of agricultural production, pointing to a strongly uneven development of the municipalities. A striking aspect that was observed in general is the marked reduction in productive diversification, and this process also occurred in a very different way in the set of 217 municipalities in the State. An important dimension that was opposed to this reduction in productive diversification is the concomitant drop in the capacity for absorbing labor by agricultural establishments and this is more pronounced in municipalities that have a more concentrated productive structure.